(untitled) (Fiep Bulletin - online, 2014)
The Physical Education and School Sport seek to promote a link between sports and training of individuals, their character, ethics, discipline, multiculturalism, among others. Thus we seek to systematize in physical education classes and workshops in sports based on the principles and ideals of Olympism, the Olympic Education program which aims to develop the Olympic values ??mainly in the contexts of lessons/training. This study deals with an action research because it is held in a pre -determined and can be further treated as a longitudinal study, your goal is to increase knowledge about a particular subject, students are involved in the early years and final years of primary school who are enrolled in the workshops of sports. We understand that the program has achieved its proposed seeking through Olympic Education ransom of basic human values??, respect for rules, opponents and colleagues, fair play and ethics in sports, values ??that begin in of sports courts, fields, running tracks, to life making them better human beings for yourself and your company.